Clinical Manifestations, Hematology, and Chemistry Profiles of the Six Most Common Etiologies from an Observational Study of Acute Febrile Illness in Indonesia. (4th October 2017) - Kosasih, Herman; Karyana, Muhammad; Lokida, Dewi; Alisjahbana, Bachti; Tjitra, Emiliana; Gasem, Muhammad Hussein; Aman, Abu Tholib; Merati, Ketut Tuti; Arif, Mansyur; Sudarmono, Pratiwi; Suharto, Suharto; Lisdawati, Vivi; et al.
Abstract: Background: Infectious diseases remain a significant healthcare burden in the developing world. In Indonesia, clinicians often manage and treat patients solely based on clinical presentations since the diagnostic testing capacities of hospitals are limited. Unfortunately, the most common infections in this tropical environment share highly similar manifestations, complicating the identification of etiologies and leading to the misdiagnosis of illness. When pathogen-specific testing is available, generally at top-tier specialist hospitals, the limited range of tests and slow turnaround times may never lead to a definitive diagnosis or improved patient outcomes. Methods: To identify clinical parameters that can be used for differentiating the most common causes of fever in Indonesia, we evaluated clinical data from 1, 486 acute febrile patients enrolled in a multi-site observational cohort study during 2013 to 2016. Results: From the 66% of subjects with confirmed etiologies, the six most common infections were dengue virus (455), Salmonella spp. (124), Rickettsia spp. (109), influenza virus (64), Leptospira spp. (53), and chikungunya virus (37). The accompanying figure shows the clinical signs and symptoms (A) and hematology and blood chemistry results (B) for the color-coded pathogens. Comparing the profiles of all infected subjects reveals parameters that are uniquely associated with particular pathogens, such as leukopenia with dengue virus. Conclusion: These observations will assist clinicians in healthcare systems with limited diagnostic testing capacities and may be useful in formulating diagnostic algorithms for Indonesia and other developing countries. Disclosures: All authors: No reported disclosures.